The value of CEOs with multi-organizational working experience: Evidence from merger and acquisition performance of Chinese Internet companies - Li, Yunrou (2021)
This study aims to investigate how multiorganizational experience of CEOs creates value in mergers and acquisition. In order to test the hypotheses, the method of event study and the variable cumulative abnormal returns are used to measure the merger and acquisition performance. Accessed from the WIND database and CSMAR Solution database, the data of both acquisition and organization is drawn from China Internet industries between 2014 and 2018, with a sample of 147 merger and acquisition events initiated by 122 firms. Based on the empirical results, it is found that consistent with the hypotheses, the multiorganizational experience of CEOs is positively related to acquisition performance and, especially, that the multi-industry experience of CEOs leads to better performance in diversifying acquisitions than in related acquisitions. This paper provides contributes to the corporate strategy literature by suggesting that as a valuable and competitive source, the multiorganizational experience can help the CEOs to lead mergers and acquisitions more effectively and ﬂexibly.